Development Policies of the Micro, Small, and Medium Enterprises (SMEs) for Improving Regional Competitiveness - Sartono; Zalviwan, M.; Octaviani, Dina; Hendharsa, Angga; Afif, Ali; Sugiardi, Sigit (Jurnal AGRISEP, 2024)
This study explores the importance of developing Micro, Small and Medium Enterprises (SMEs) and the creative economy, as well as their position as the main drivers of economic growth. Focusing on North Kayong District, West Kalimantan, Indonesia, this research highlights the resilience and innovation demonstrated by SMEs in overcoming challenges. Government initiatives target the mitigation of barriers, with an emphasis on developing local superior products to increase regional competitiveness. The main objective is to utilize local potential to create sustainable opportunities for economic expansion and poverty alleviation. Qualitative research methods, through observation, focus group discussions (FGD), and questionnaires, as well as data analysis techniques including difference tests and SWOT analysis. The research results show that there are significant differences between government policies and the expectations of SMEs, while the results of the SWOT analysis show that SMEs have strengths to be developed such as the availability of local raw materials and market uptake, but have challenges such as limited access to funding, infrastructure, training and promotion. product. The position of SMEs is in quadrant two, the most appropriate diversification strategy, including product, market and place diversification. Government mitigation to support the development of SMEs, through policies developing road and transportation infrastructure to facilitate access to products and markets, providing markets for sales of superior products, training facilities for SMEs. The impact on local communities is as a provider of raw materials, developing SMEs and the creative economy, as well as increasing the economy and regional competitiveness.